La reforma legal del FAD: dos visiones, dos fondos, se aleja la coherencia - Martínez Osés, Pablo José (Revista Española de Desarrollo y Cooperación, 2023)
Since social organizations begin to systematically address the monitoring of Spanish international cooperation policy, FAD has been at the center of their complaints. The dual purpose intended by the constitution of the instrument from its inception has been nothing short of a major headache for government managers. The dual mandate of the instrument should, on one hand, clearly contribute to the purposes of development while, on the other, be a tool for the promotion of Spanish exports.